In memoriam – Степан Стойко - Bedernichek, Tymur (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
On October 22 of this year, professor Stepan Stoyko – a prominent Ukrainian scientist and nature conservationist, died at the age of 100. Until his last days, he had a clear mind, was active in nature conservation, and continued working on academic publications. His last research article was published in September 2020, approximately one month before his death. For decades he was a principal investigator and head of a department in the State Museum of Natural History and the Institute of Ecology of the Carpathians. Stepan Stoyko created many protected areas, including the Carpathian State Reserve (Carpathian Biosphere Reserve), Roztochya Nature Reserve, and Carpathian, Yavorivskyi, Shatsky, Uzhansky, Skole Beskids, and Synevyr national nature parks. After the catastrophic floods in Transcarpathia in 1998, and 2001, he brought attention to clear-cutting, including the Carpathian forests’ illegal cutting. In his late 90s, Stepan Stoyko supported the initiative group Free Svydovets that protected one of the most important biodiversity islands in the Ukrainian Carpathians – Svydovets mountain range. His support was crucial to prevent building the largest Carpathian ski resort and conserve unique mountain old-growth forests, sub-alpine, and alpine grasslands. I knew Stepan Stoyko for over 20 years since I was 15 years old. Here I would like to share my perspective on his contribution to nature conservation and environmental science. To commemorate his scientific life and contributions, the Ukrainian community of botanists and ecologists Dovkolabotanika established Stepan Stoyko Award in the fields of nature conservation and environmental science for undergraduate, graduate, and PhD students.